2011
DOI: 10.1002/smll.201001832
|View full text |Cite
|
Sign up to set email alerts
|

Polymorph‐ and Size‐Dependent Uptake and Toxicity of TiO2 Nanoparticles in Living Lung Epithelial Cells

Abstract: The cellular uptake and distribution of five types of well-characterized anatase and rutile TiO(2) nanoparticles (NPs) in A549 lung epithelial cells is reported. Static light scattering (SLS), in-vitro Raman microspectroscopy (μ-Raman) and transmission electron spectroscopy (TEM) reveal an intimate correlation between the intrinsic physicochemical properties of the NPs, particle agglomeration, and cellular NP uptake. It is shown that μ-Raman facilitates chemical-, polymorph-, and size-specific discrimination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 43 publications
7
75
0
Order By: Relevance
“…Higher zeta potentials suggest increased repelling force among particles, thereby forming fewer agglomerates. Since the agglomerates are more easily taken up by the cell via endocytic transport than individual NPs (Andersson et al, 2011), our results of reduced penetration of the CM-NPs could be explained by decreased degree of agglomeration, likely due to fatty acid-associated surface modification. Future studies should be carried out to understand possible changes in the charge, subcellular distribution, zeta potential and agglomerate formation of TiO 2 NPs coated with fatty acids.…”
Section: Discussionmentioning
confidence: 76%
“…Higher zeta potentials suggest increased repelling force among particles, thereby forming fewer agglomerates. Since the agglomerates are more easily taken up by the cell via endocytic transport than individual NPs (Andersson et al, 2011), our results of reduced penetration of the CM-NPs could be explained by decreased degree of agglomeration, likely due to fatty acid-associated surface modification. Future studies should be carried out to understand possible changes in the charge, subcellular distribution, zeta potential and agglomerate formation of TiO 2 NPs coated with fatty acids.…”
Section: Discussionmentioning
confidence: 76%
“…Several other studies clearly indicate that size is an important parameter for uptake. 25,[50][51][52] It is difficult to say if the difference in the degree of uptake was size-related in our study, since the primary particle size range was small. 25,[50][51][52] However, small primary NPs are taken up by other mechanisms than larger particles or agglomerates of the same compound.…”
Section: Cellular Uptake Of Tio 2 Npsmentioning
confidence: 70%
“…The aggregation may affect the cellular uptake as Andersson et al [56] found NP uptake was strongly dependent on the agglomeration size, not the primary particle size. This proved serendipitous as the concentration of LDH NPs used in cellular uptake studies did not typically exceed 40 lg/mL so as to circumvent unwanted NP aggregation.…”
Section: Suspension Stability Of Sldh and L-ldh Npsmentioning
confidence: 99%